Sex differences in the spatial distribution of bone in relation to incident hip fracture: Findings from the AGES-Reykjavik study - Marques, Elisa A. (Bone, 2018)
In this case-cohort study, we used data-driven computational anatomy approaches to assess within and between sex spatial differences in proximal femoral bone characteristics in relation to incident hip fracture. One hundred male and 234 female incident hip fracture cases, and 1047 randomly selected noncase subcohort participants (562 female) were chosen from the population-based AGES-Reykjavik study (mean age of 77 years). The baseline –i.e. before hip fracture– hip quantitative computed tomography scans of these subjects were analyzed using voxel-based morphometry, tensor-based morphometry, and surface-based statistical parametric mapping to assess the spatial distribution of volumetric bone mineral density (vBMD), internal structure, and cortical bone properties (thickness, vBMD and trabecular vBMD adjacent to the endosteal surface) of the proximal femur, respectively, in relation to incident hip fracture. Results showed that in both men and women: 1) the superior aspect of the femoral neck and the trochanteric region (except for cortical bone thickness) were consistently identified as being associated with incident hip fracture, and 2) differences in bone properties between noncases and incident hip fracture cases followed similar trends, were located at compatible regions, and manifested heterogeneity in the spatial distribution of their magnitude with focal regions showing larger differences. With respect to sex differences, most of the regions with a significant interaction between fracture group and sex showed: 1) differences of greater magnitude in men between noncases and incident hip fracture cases with different spatial distributions for all bone properties with the exception of cortical bone thickness, and 2) that while most of these regions showed better bone quality in male cases than in female cases, female cases showed higher vBMD in the principal compressive group and higher endotrabecular vBMD at several regions including the anterior, posterior, and lateral aspects of the proximal femur. These findings indicate the value of these image analysis techniques by providing unique information about the specific patterns of bone deterioration associated with incident hip fracture and their sex differences, highlighting the importance of looking to men and women separately in the assessment of hip fracture risk.